CPC-055 Evaluation of Treatment Compliance in Multiple Sclerosis Patients and Its Impact on the Clinical Stabilisation of the Disease. (12th March 2013) - Rodrigues, AI; Fernandes, AF; Marques, R
Abstract : Background: Multiple sclerosis is a degenerative disease in which compliance with therapeutic regimens is extremely important in the clinical stabilisation of disease. Purpose: To evaluate the compliance of patients with treatment and the impact it has on the clinical stabilisation of the disease. Materials and Methods: Data were collected using a patient survey and consulting the hospital computer system. Statistical analysis was done with SPSS. The following data were collected: number of patients, average age, number of outbreaks and management failures in the last six months, reason for failure and flaws in the administration of medicines reported in the survey. Results: The sample (97 patients, mean age 41.73 ± 9.37 years old) was not only representative of the total MS patients followed in Centro Hospitalar Leiria-Pombal (CHLP) but also of the epidemiological data on the disease. Over the past six months, 18.6% of patients had at least one outbreak. Regarding administration failures, 24.7% of patients admitted to failing to administer their medicines at least once, 45.8% of these failed more than three times. The main reason for failing to administer the treatment was patient oversight and that represented 48% of total failures. The largest number of administration failures was observed in patients treated with Interferon B 1b 8 MIU (66.7%). 86.6% of patients had administered their medicine correctly. In this group of patients, there is no statistically meaningful correlation between the failures of management and inventory, with the number of outbreaks that occurred. Conclusions: Generally, multiple sclerosis patients followed in CHLP are a group with a great commitment to following their treatment. There was a significant percentage of people who failed to administer all doses correctly, although there is no statistically meaningful correlation with the number of outbreaks that occurred, and there was a significant incidence of outbreaks in the last 6 months, suggesting that the disease has a multifactorial nature. As I see it, the pharmaceutical staff plays an essential role in promoting compliance, which is crucial for stabilising the patients' clinical condition. No conflict of interest.